Pendampingan pembuatan bahan bakar gas dari Biomassa menggunakan Teknologi Gasifikasi - Fajri Vidian; Heni Fitriani; Helmy Alian; Taufik Arief; Qomarul Hadi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
The utilization of new and renewable energy is of paramount importance considering the limited reserves of fossil fuels and the negative impacts resulting from their usage. Biomass presents an intriguing option as it can be renewed and is abundantly available in Indonesia. Gasification technology stands as one of the thermochemical methods to convert biomass into gas fuel. This process demonstrates high efficiency and generates low pollution. However, the knowledge of this technology remains confined to certain scientists and practitioners, necessitating the need for socialization and information dissemination, particularly in rural areas. Consequently, demonstrations and training sessions were conducted for the community in Kerinjing Village, Ogan Ilir, South Sumatra. The demonstrations involved students who were trained to operate gasification equipment, with approximately 30 participants attending the training sessions. Additionally, presentations and discussions were held to elucidate the potential of biomass as gas fuel, the main components of gasification apparatus, and the process of converting biomass into gas fuel. The results of the demonstrations revealed a high level of enthusiasm among the residents of Kerinjing Village toward gasification technology. The residents displayed an easy grasp of the straightforward equipment operation and their ability to produce such equipment themselves due to its accessibility and ease of fabrication. The use of simple language in delivering information facilitated the comprehension of gasification technology among the community. In conclusion, gasification technology offers a simple yet promising approach to serve as an alternative energy solution in rural areas. Continuous demonstrations and socialization efforts are imperative to promote wider implementation of this technology, thereby advancing the adoption of new and renewable energy sources. Consequently, it is hoped that this initiative will address the constraints posed by limited fossil fuel reserves and contribute to sustainable development